Eosinophil Cationic Protein in Patients with Differentiated Thyroid Cancer Treated with Radioactive Iodine 131 - Zivancevic-Simonovic, Snezana; Mihaljevic, Olgica; Kostic, Irena; Ilic, Nevenka; Mihajlovic, Dusan; Vasiljevic, Dragan; Mijatovic-Teodorovic, Ljiljana; Miletic-Drakulic, Svetlana; Colic, Miodrag (Annals of clinical and laboratory science, 2017)
Published data indicate the involvement of eosinophil granulocytes and eosinophil cationic protein (ECP) in tumor defense. The aim of this study was to analyze serum ECP concentrations in patients with differentiated thyroid cancer (DTC) before, 3 days and 7 days after radioactive iodine (131-I) therapy. Association of ECP concentrations with histological type of tumor, stage of disease and/or levels of selected T-helper 2 (Th2) cytokines was examined. The study population included 17 DTC patients and 10 control subjects. ECP was measured by fluoroimmunoassay (FIA). Th2 (cytokines interleukin 4 (IL-4), interleukin 5 (IL-5), and interleukin 13 (IL-13)) were determined by enzyme-linked immunosorbent assays (ELISA). We found that ECP values in DTC patients before radioactive iodine therapy were approximately two-fold higher than in the controls, but the difference was statistically significant only if the patients with DTC and associated Hashimoto thyroiditis (HT) were included. There was no correlation between the serum concentrations of IL-5 and ECP. Radioactive iodine therapy led to a decrease in serum ECP level which did not follow the decline in serum protein levels. Additional studies are needed to determine the significance of these findings.